Türkiye'de Kamusal Müzakere Deneyimleri: Batman Üniversitesi Çalıştay Örneği - Hekimoğlu, Gülsüm (Muş Alparslan Üniversitesi, 2019)
Changesin social problems with changing society. Today's societies may seem morefortunate than past societies. However, every society has its own problems.Communicative democracy and equal participation are the most sensitive problemsof today's societies. Representative democracy, excludes individuals from basicdemocratic processes and removes citizens from participatory actions. Thisstudy aims to evaluate the alternative options that can overcome theinequalities arising from the results of representative democracy. For thispurpose, in the study, a scientific meeting in the university was evaluated interms of the public negotiation experience. The study includes a discourseanalysis prepared by qualitative research method. Such a space for discursiveinteraction has not been able to overcome the crisis of representativedemocracy and overcome the inequalities arising from force asymmetries, despitethe fact that it offers individuals the opportunity to express their ideas andto meet rival ideas and, moreover, has the potential to act together on theirshared lives.

Değişen toplumla birlikte sosyalproblemlerde değişmektedir. Günümüz toplumları geçmişteki toplumlara oranladaha talihli görünebilir. Ancak her toplum kendine özgü problemlere sahiptir.İletişimsel demokrasi ve eşit katılım, günümüz toplumlarının en hassasproblemlerindendir. Temsili demokrasi, bireyleri temel demokratik süreçlerdendışlamakta ve yurttaşları katılımcı eylemlerden uzaklaştırmaktadır.  Bu çalışma temsili demokrasinin sonuçlarındankaynaklanan eşitsizliklerin üstesinden gelebilecek alternatif seçeneklerideğerlendirmeyi amaçlamaktadır. Bu amaç doğrultusunda, bu çalışmada, üniversitedeki bir bilimsel toplantı kamusal müzakere deneyimi açısındandeğerlendirilmiştir. Çalışma, nitel araştırma yöntemi ile hazırlanmış birsöylem analizini içermektedir. Böylesi bir söylemsel etkileşim mekânı, bireylere fikirlerini ifade edebilme ve rakip fikirlerle karşılaşma imkanısunmasına ve dahası ortak yaşamlarıyla ilgili birlikte eyleme potansiyelitaşımasına rağmen, temsili demokrasinin bunalımını aşamamış ve güçasimetrilerinden kaynaklanan eşitsizliklerin üstesinden gelememiştir.
Publıc Negotiation Experıence in Turkey: Batman Unıversıty Workshop Example
anemon
Keywords: Democratic Negotiation; Public Space; Participation; Democracy; Workshop; Demokratik Müzakere; Kamusal Alan; Katılım; Demokrasi; Çalıştay